(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Films have always been the cultural space where stereotypes are continued. Though Malayalam cinema has managed to establish its name through new themes and characters, it also continues to perpetuate the caste based marginalization and victimization. The people of the fringes become mere sidekicks or extras who have no role in both the film as well as in the society. Among them Kammattipadam stands out due to its authentic portrayal of characters and its solid premise. More than glorification, what one sees in the movie is a more realistic as well as humanistic portrayal of the Dalit.